Kajian Teoritis tentang Hukuman Pemiskinan bagi Pelaku Korupsi - Dewi Amalia (Majelis: Jurnal Hukum Indonesia, 2024)
This article discusses a theoretical study of impoverishment punishment for corrupt perpetrators. Corruption is considered a planned crime that has a negative impact on the state and society and requires decisive action to eradicate it. This survey revealed that the majority of students think that impoverishment punishment, which is expected to have a deterrent effect compared to prison sentences, can be an effective preventive effort in eradicating corruption. The students also emphasized the importance of returning assets to the state to compensate for losses due to corruption. The view of the death penalty for corruption perpetrators is now considered irrelevant, because the focus is on recovery economy and justice. This study shows that a stricter and more systematic approach is needed in eradicating corruption, including stricter regulations, proper asset management, and educating the public about the negative impacts of corruption. Thus, this article presents an understanding of sharing perspectives. The younger generation can help create more effective anti-corruption policies in Indonesia.